2017
DOI: 10.3390/brainsci7120156
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Depression: The Intersections of Race, Gender, and Socioeconomic Status

Abstract: Background: Despite the wealth of literature on social determinants of mental health, less is known about the intersection of these determinants. Using a nationally representative sample, this study aimed to study separate, additive, and multiplicative effects of race, gender, and SES on the risk of major depressive episode (MDE) among American adults. Methods: National Survey of American Life (NSAL) included 3570 African Americans and 891 Whites. Race, gender, socioeconomic status (SES, household income, educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
169
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(178 citation statements)
references
References 74 publications
8
169
1
Order By: Relevance
“…Food insecurity and poor access to health care were also associated with depression in at least three sites. As reported in other low‐income countries, socioeconomic status was associated with depression in adolescents . Although mostly implemented in high‐income countries, studies show that living with the single parent is a risk of depression .…”
Section: Discussionmentioning
confidence: 64%
“…Food insecurity and poor access to health care were also associated with depression in at least three sites. As reported in other low‐income countries, socioeconomic status was associated with depression in adolescents . Although mostly implemented in high‐income countries, studies show that living with the single parent is a risk of depression .…”
Section: Discussionmentioning
confidence: 64%
“…These results suggest that long term economic processes are involved in shaping Minorities' Diminished Return, and some of these processes start early in life. These findings are important because family SES is a major contributor to racial health disparities during childhood (Assari et al 2018;Assari 2017f). Our study showed that each SES indicator reflected lower SES decades later for Black than White families.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, income better reduces number of chronic condition and depression for whites than minority groups. Among blacks, highly educated individuals may be at an increased risk of mental health problems . Although the exact causes are unknown, differential treatment by the society can cause educational attainment to show stronger effects on income and purchasing power for non‐Hispanic whites than for ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%